Hubungan Stres dengan Risiko Penyakit Kardiovaskuler pada Perawat Rumah Sakit - Arifin, Samsul; Tualeka, Abdul Rohim (Preventia: The Indonesian Journal of Public Health, 2019)
Nurseis a profession that has a high stress level. High stress is thought to play a role in causing cardiovascular disease. This study aims to analyze the relationship between work stress and cardiovascular risk. A cross sectional study design. Respondents were all nurses of Malang Islamic Hospital as many as 84 people. Chi Square test is used to determine the relationship of work stress levels with the risk of cardiovascular disease. Most nurses have an abnormal stress that is equal to 72.6% or 61 nurses. Mostof them have a low risk of 90.5% or 76 people. The number of nurses who have abnormal stress has a higher risk of cardiovascular disease that is 11.5% compared to nurses who have normal stress which is 4.3%. Chi Square test results of a significance valueof 0.321 means greater than 0.05 so it can be concluded that there is no significant relationship between the level of work stress with the risk of cardiovascular disease.